2020
DOI: 10.1111/jth.14990
|View full text |Cite
|
Sign up to set email alerts
|

A new pedigree with thrombomodulin‐associated coagulopathy in which delayed fibrinolysis is partially attenuated by co‐inherited TAFI deficiency

Abstract: Background Thrombomodulin‐associated coagulopathy (TM‐AC) is a rare bleeding disorder in which a single reported p.Cys537* variant in the thrombomodulin gene THBD causes high plasma thrombomodulin (TM) levels. High TM levels attenuate thrombin generation and delay fibrinolysis. Objectives To report the characteristics of pedigree with a novel THBD variant causing TM‐AC, and co‐inherited deficiency of thrombin‐activatable fibrinolysis inhibitor (TAFI). Patients/methods Identification of pathogenic variants in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 17 publications
(90 reference statements)
1
32
2
Order By: Relevance
“…The obvious consideration is related to therapy with heparin to limit coagulopathy. However, to degrade pre‐existing fibrin in the lung it is essential to promote local fibrinolysis and a nebulizer form of tissue‐type plasminogen activator (tPA) to treat COVID‐19 has been recently proposed 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The obvious consideration is related to therapy with heparin to limit coagulopathy. However, to degrade pre‐existing fibrin in the lung it is essential to promote local fibrinolysis and a nebulizer form of tissue‐type plasminogen activator (tPA) to treat COVID‐19 has been recently proposed 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with mouse experiments that did not find an effect of TAFI deficiency on the hemostatic capacity, 26 subjects with only this genetic variation, but no thrombomodulin alterations, were asymptomatic. 25 To the best of our knowledge, no bleeding disorders related to a gain-of-function mutation in plasminogen have been described in humans.…”
Section: E S Tab Lis Hed Hyperfib Rinoly Tic B Leed Ing D Isorder Smentioning
confidence: 99%
“…Alterations in factors and regulators of the fibrinolytic system have been identified in both case series and families with a pattern of de- factors, as only few genetic confirmations for PAI-1 deficiency have been described. [22][23][24] Recently, Westbury et al 25 identified, in a family with a thrombomodulin-associated bleeding disorder, a stop-gain mutation in the CPB2 gene that encodes TAFI and resulted in 50% lower TAFI levels. Consistent with mouse experiments that did not find an effect of TAFI deficiency on the hemostatic capacity, 26 subjects with only this genetic variation, but no thrombomodulin alterations, were asymptomatic.…”
Section: E S Tab Lis Hed Hyperfib Rinoly Tic B Leed Ing D Isorder Smentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding complications related to CPU inhibition have neither been reported in cpb2 knockout mice nor after administration of CPU inhibitors. Westbury et al recently showed that hemostasis was not significantly impacted in individuals with a partial proCPU deficiency, which underscores the potential of pharmacological inhibition of CPU for the treatment of thromboembolic diseases and encourages that this therapeutic strategy will unlikely result in bleeding complications [197,198]. However, data need to be interpreted with caution as only limited activation of proCPU (1-2%) can be enough to exert its antifibrinolytic effects.…”
Section: Potential Benefit Of the Use Of Cpu Inhibitors-overview On Imentioning
confidence: 99%